Lattice boltzmann method on flow in microchannel - Ng, Chee Horng (2009)
A lattice Boltzmann algorithm to model the fluid flow in microchannel is developed. The details in determining the parameters critical fo r lattice Boltzmann application in microchannel flow are provided. Our results from a 9-bit square lattice Boltzmann model are in good agreement with recent analytical data fo r a pressure-driven microchannel flow in slip flow regime. The differences between the predicted and the analytical fo r pressure gradients along the channel are well comparable. Results suggest that the lattice Boltzmann model described here is an effective computational tool fo r predicting more complex microfluidic systems that might be problematic using conventional methods.